2022
DOI: 10.1108/bepam-05-2022-0069
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of planning function management in Vietnam’s public construction works

Abstract: PurposeThe planning function is a central component of management principles, enabling the success of construction project management. Many works have been highlighting the topic of critical success factors within construction organizations, yet the results have rarely covered planning behaviors within public construction work management; these less investigated areas were the aims of this study.Design/methodology/approachTo fulfill this research aim, seven attributes of planning function were first derived th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Recent studies on the Vietnamese construction industry identified several factors, including KM and project performance [81]. Several authors identified sourcing expertise, technology utilization for information and knowledge sharing [82,83], management effectiveness [84], human resources development [85,86], financial capacity [86,87], teamwork [88], and soft skills [89] as key pillars affecting construction project performance (Table 1). Moreover, in construction project management, previous studies stated that unskilled labor, workmanship, poor design capabilities, and obsolete construction technology impact an organization's ability to manage complex projects in Vietnam [11].…”
Section: A Case Of the Vietnamese Construction Industrymentioning
confidence: 99%
“…Recent studies on the Vietnamese construction industry identified several factors, including KM and project performance [81]. Several authors identified sourcing expertise, technology utilization for information and knowledge sharing [82,83], management effectiveness [84], human resources development [85,86], financial capacity [86,87], teamwork [88], and soft skills [89] as key pillars affecting construction project performance (Table 1). Moreover, in construction project management, previous studies stated that unskilled labor, workmanship, poor design capabilities, and obsolete construction technology impact an organization's ability to manage complex projects in Vietnam [11].…”
Section: A Case Of the Vietnamese Construction Industrymentioning
confidence: 99%